Synthesis and Characterization of Palladium(II) Complexes with Thiosemicarbazones - Sultana, Samim; Baruah, Jayantajit; Borah, Geetika (Asian Journal of Chemistry, 2018)
Three new complexes viz., [PdCl2(H-aatp)2] (1), [Pd(dmbptz)2] (2) and [Pd(btz)] (3) have been synthesized by reacting [PdCl2(cod)] with the ligands H-aatp, H-dmbptz and H2-btz, respectively (where H-aatp = anisaldene-4-aminothiophenol; H-dmbptz = 2,5-dimethoxybenzyl-4-phenylthiosemicarbazone and H2-btz = benzil-bisthiosemicarbazone). These have been characterized by various physico-chemical techniques such as FTIR, UV-visible, 1H and 13C NMR, ESI(+)-mass spectroscopy, etc. The complexes were found to be diamagnetic, four coordinated mononuclear neutral molecules with square planar or distorted square planar geometry.